Quantitative and quality losses caused by rodents in on-farm stored maize: a case study in the low land tropical zone of Kenya - Ognakossan, Kukom Edoh; Mutungi, C.M.; Otieno, T.O.; Affognon, Hippolyte D.; Sila, D.N.; Owino, W.O. (Springer, 2018)
Rodents are one of the major storage pests in on-farm maize storage in the tropics. However, information on actual magnitude of weight and quality losses caused by rodents in maize stores and species of rodent associated with the losses is scarce and if available would help to improve maize postharvest management. Maize stores of small-scale farmers in the lowland tropical zone of Kenya were monitored for actual weight losses caused by rodents and rodent trapping was conducted to determine species and estimate population of the rodents associated with the losses. Moulds and total aflatoxin contamination and nutritional value of rodent-damaged grain and non-damaged grain samples were also compared to evaluate the impact of rodent infestation on grain quality. In a sample of 20 farmers, we found that cumulative weight losses due to rodents ranged from 2.2 to 6.9% in shelled maize grain and from 5.2 to 18.3% in dehusked cobs after storage for 3 months. Rattus rattus was the only rodent species captured over the whole trapping period with a trap success rate of 0.6–10.0%. Total mould count, Fusarium spp. incidence and total aflatoxin contamination were significantly higher in rodent-damaged grains than in the non-damaged ones whereas no significant differences were observed for the incidence of Aspergillus spp. There were also significant decreases in dry-matter, fat, crude protein and fatty acid content in rodent-damaged grain compared to non-damaged grain. These findings show that rodents are a significant cause of postharvest losses in on-farm maize storage and impact negatively on food nutrition and safety. Mitigation strategies for postharvest losses should therefore include rodent control.